Economic growth in Europe : a comparative industry perspective - Timmer, Marcel (Cambridge : Cambridge University Press, 2010)
Why has European growth slowed down since the 1990s while American productivity growth has speeded up? This book provides a thorough and detailed analysis of the sources of growth from a comparative industry perspective. It argues that Europe's slow growth is the combined result of a severe productivity slowdown in traditional manufacturing and other goods production, and a concomitant failure to invest in and reap the benefits from Information and Communications Technology (ICT), in particular in market services. The analysis is based on rich new databases including the EU KLEMS growth accounting database and provides detailed background of the data construction. As such, the book provides new methodological perspectives and serves as a primer on the use of data in economic growth analysis. More generally, it illustrates to the research and policy community the benefits of analysis based on detailed data on the sources of economic growth.
Introduction and overview -- Economic growth in Europe -- EU KLEMS database -- Structural change -- The industry origins of aggregate growth -- Productivity levels and convergence -- Drivers of productivity growth in Europe.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Industrial policy -- Europe -- Case studies; Technological innovations -- Economic aspects -- Europe -- Case studies; Europe -- Economic conditions -- 20th century -- Case studies; Europe -- Economic conditions -- 21st century -- Case studies